1936
DOI: 10.2134/agronj1936.00021962002800070005x
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Efficiency of Free and Combined Nitrogen for the Nutrition of the Soybean1

Abstract: R ECENT agronomic studies on pasture mixtures supplied various fertilizers indicate that leguminous plants are apparently unable to compete successfully with nonleguminous crops in the presence of an adequate supply of fixed available nitrogen. This fact might be interpreted to mean that the products of symbiotic nitrogen fixation are better suited for the development of leguminous plants than are the products elaborated from combined sources. On the other hand, it is well established that a supply of fixed ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

1937
1937
1984
1984

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…T HE soybean (Glycine max L.) plant, like other legumes, has available two options in obtaining sufficient N for growth and reproduction: N fixation or absorption and assimilation of inorganic N. The extent to which each of these processes contributes to the growth and productivity of soybeans has been studied by various methods for several years (10,12,17). Experiments involving different levels of 1 5Ntagged inorganic N (12) showed that, as inorganic N concentration was increased, total N assimilated increased but the proportion assimilated via fixation decreased.…”
mentioning
confidence: 99%
“…T HE soybean (Glycine max L.) plant, like other legumes, has available two options in obtaining sufficient N for growth and reproduction: N fixation or absorption and assimilation of inorganic N. The extent to which each of these processes contributes to the growth and productivity of soybeans has been studied by various methods for several years (10,12,17). Experiments involving different levels of 1 5Ntagged inorganic N (12) showed that, as inorganic N concentration was increased, total N assimilated increased but the proportion assimilated via fixation decreased.…”
mentioning
confidence: 99%
“…A soja pode rapidamente utilizar tanto o N simbiótico quanto o disponível no solo (2,6,8,11,13), mas a quantidade de N simbiótico produzida é inversamente proporcional à quantidade de N disponível (1,2,13). Quando suprido em quantidades que excedam as necessidades para o crescimento da planta, o N pode impedir a fixação simbiótica (2,12).…”
Section: Introductionunclassified